1996
DOI: 10.1677/joe.0.1500099
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of fumagillin and its analogue TNP-470 on the function, morphology and angiogenesis of an oestrogen-induced prolactinoma in Fischer 344 rats

Abstract: The process of angiogenesis occurs in many physiological states, but it is also essential for the growth of solid tumours and metastasis formation. An abnormal arterial vascularization has been shown in prolactin-secreting pituitary adenomas induced by prolonged treatment with oestrogens in Fischer 344 (F344) rats. It is thought that anti-angiogenic agents might be useful in therapy for these tumours. Fumagillin and its analogue TNP-470 are known to inhibit endothelial cell proliferation selectively, but their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 24 publications
(27 reference statements)
1
20
0
Order By: Relevance
“…Thus, it is interesting to note that anti-angiogenic inhibitors such as fumagillin and its analogue TNP-470 have antitumor and antiprolactin activity in the experimentally estrogen-induced pituitary adenoma in F 344 rats. The inhibition of angiogenesis was suggested to be the major cause [14]. The above findings together with the fact that some patients respond to bromocriptine treatment while others do not are in line with the hypothesis that prolactinoma is a heterogeneous disorder [6,15] with complicated and multifactorial etiology and pathogenesis.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Thus, it is interesting to note that anti-angiogenic inhibitors such as fumagillin and its analogue TNP-470 have antitumor and antiprolactin activity in the experimentally estrogen-induced pituitary adenoma in F 344 rats. The inhibition of angiogenesis was suggested to be the major cause [14]. The above findings together with the fact that some patients respond to bromocriptine treatment while others do not are in line with the hypothesis that prolactinoma is a heterogeneous disorder [6,15] with complicated and multifactorial etiology and pathogenesis.…”
supporting
confidence: 71%
“…Many researchers consider F 344 rats to be the most sensitive strain to develop estrogeninduced prolactinoma [14,25,26] and SD rats to be relatively insensitive. This has been studied in detail by Weiner et al [27] who implanted subcutaneously 1-cm-long silastic 17-ß-estradiol (E 2 ) tubing into ovariectomized F 344 rats and SD rats.…”
Section: Animal Models For the Investigation Of Pituitary Prolactin-smentioning
confidence: 99%
“…It has also been shown that angiogenesis is essential for the growth of oestrogen-induced prolactin-secreting anterior pituitary tumours (Elias & Weiner 1984). It was recently demonstrated that fumagillin and its analogue TNP-470, which are known to selectively inhibit endothelial cell proliferation, inhibited prolactin production and prolactotrophic cell density and proliferation and suppressed neovascularisation in Fischer 374 rats bearing prolactinomas induced by oestrogen treatment (Takachi et al 1994, Stepien et al 1996. These results provide strong evidence for the anti-prolactinoma effects of inhibitors of angiogenesis in this pituitary prolactinoma model.…”
Section: Growth Factors and Their Receptors Involved In Modulating Anmentioning
confidence: 78%
“…It has also been found that the vascular density was higher in gonadotropinomas that in the non-tumoral anterior pituitary gland (42). The inhibitors of angiogenesis are effective in the suppression of growth of the experimental pituitary tumour (43,44), and the levels of angiogenic cytokines VEGF and bFGF are elevated in the peripheral blood of patients with pituitary adenomas (45). However, Gorczyca & Hardy (46) in angiographic studies detected the presence of additional arteries (which were not part of the portal system) in 66% of their patients with microadenomas of this organ, while Farnoud et al (47) observed changes characteristic for increased vasculogenesis in the basal membrane surrounding cells of pituitary tumours in humans.…”
Section: Angiogenesis and Neoplasms Of Endocrine Glandsmentioning
confidence: 99%